Faktor-Faktor yang Memengaruhi Kejadian Berat Badan Lahir Rendah Di Indonesia Tahun 2020 - Tantri Retno Anasthasia; Efri Diah Utami (Seminar Nasional Official Statistics, 2022)
The infant mortality rate can reflect the state of the health status of a community. The biggest cause of infant mortality in Indonesia is the incidence of LBW. The incidence of LBW is still a problem in Indonesia because there are still several provinces that have LBW numbers above the national average. The data used are secondary data from SUSENAS 2020. The statistical method used is descriptive analysis which is used to find out the general description of the incidence of LBW in Indonesia and inferential analysis which uses binary logistic analysis to determine the factors that affect the incidence of LBW. The results of this study indicate that from 7,209,181 babies born two years ago or less, there were 11.69 percent of babies born with LBW conditions. Based on the results of binary logistic analysis, it was found that the age of first pregnancy, place of delivery, sanitation conditions, drinking water conditions and maternal smoking status had a significant effect on the incidence of LBW.